Pengaruh Perbedaan Setting Kedalaman Perairan pada Pengoperasian Alat Tangkap Pancing Ulur terhadap Ikan Kerapu (Epinephelus Sp.) di Perairan Pantai Pengambengan - Gusman Ilham Widiantoro; M Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
Long fishing is an environmentally friendly traditional fishing tool that is commonly used by fishermen to catch fish passively using bait, both in sandy waters and in coral reef areas. Grouper fish (Epinephelus sp.) tend to inhabit waters of a certain depth, especially in areas of coral fractures and dead corals that serve as shelter and foraging. Determining the right depth setting in the operation of a fishing rod is essential to optimize the catch. This study aims to determine the effect of the difference in setting depth on grouper fish catch in the waters of Pengambengan Beach and determine the most effective depth. The study used an experimental method with three depth treatments, namely 10 m, 15 m, and 20 m, each repeated nine times. Data analysis was carried out by Group Random Design (RAK) and ANOVA test. The results showed that a depth of 10 m produced the highest catch with a total of 35 fish (average 3.89 fish/trip), followed by a depth of 15 m with 10 fish (average 1.11 fish/trip), and a depth of 20 m with 7 fish (average 0.78 fish/trip). Statistically, the difference in depth has a real influence on the number of grouper catches. A depth of 10 m is recommended as the optimal setting for the operation of long fishing rods in the waters of Pengambengan Beach.